Developing of a device for measuring the areal distribution of the forces in the contact zone of foot and underground for the use in leg prostheses - Kubisch, Jörg (2020)
The presented work demonstrates the process of designing a cheap, low cost three axis force sensor. Further it describes its integration in an array of multiple sensors to measure the distribution of forces acting on the sole of a prosthetic foot. The focus will be on easy manufacturing and common materials since the sensor will be integrated in a low cost prosthesis for lower limp amputees. Using the knowledge from bio mechanics and some basic assumptions for the later use, requirements for the project are derived. After a presentation of some state of the art sensor principles, suitable concepts are collected. Than, the concepts are compared using a comparison table to find the one the fits the requirements the best. A very compelling concept using barometers casted in silicone rubber is tested using a simple prototype to try out whether it is a good candidate or not. The tests show that the concept is capable of measuring forces but due to its disadvantageous susceptibility for temperature changes it is rejected for the further development process. The concepts are reevaluated and a new concept is chosen. Afterwards the design process is described. Beginning with the mechanical design explaining the working principle. The calculation of the dimensions is presented. After that a circuit to work with a capacitive measurement as well as a version for resitive measurement is developed and a layout for a prototype board using capacitive measurement is proposed. To prove the functionality, the capacitive system is built up as a prototype. To try the measurement behavior and to measure its repeatability a test stand is designed. It uses commercial available load cells to conduct a reference measurement. The output of the sensor is compared to the reference measurement. With various different test procedures the curves mapping the measured values to the force for normal and shear force measurement are determined. During the tests, different aspects of performance like creep behavior or hysteresis are investigated. Also the repeatability is measured various times under different loads to make reliable estimations of the precision of the measurement. Further on, a resistive force sensor which could be used instead of the capacitive sensing elements is tested regarding its curve and performance to have a comparison of the advantages and disadvantages of either designing the future sensor with resistive or capacitive sensing elements. With both concepts a repeatability of a few percent uncertainty can be achieved. Further on ways to improve future versions of the sensor are described based on the experiences made during the work with the prototype. Finally a possible way to integrate multiple sensors into a sensing array is proposed. The design as well as possible electrics to acquire the data are discussed. This way a solid basis for further developments of a sensing array measuring the force distribution is given.